Straddling the South China Sea: Tropical Speculative Futures of Borneo and Malaysia - L. Han (eTropic: electronic journal of studies in the tropics)
In the year 2119, two sisters, Jules and Nina, live in a nation divided by the South China Sea, struggling to survive tropical environmental disasters unleashed by human-induced climate change that have exacerbated tensions between the federal government and Bornean states. Sarawak has declared independence from Malaysia and, together with Sabah, Brunei, and Kalimantan, has formed the Borneo Treaty Organisation to keep safe from other nations greedy for their natural resources and plentiful land fortified against the rising seas. The West Malaysians call this a “Civil War”; the Sabahans and Sarawakians call it the “War of Independence”. During a negotiated ceasefire, Malaysia, Sabah, and Sarawak each welcome their people home; in the case of the once Bornean Malaysian states, people return to embrace citizenship of the newly independent Sabah and Sarawak. In Sarawak, Jules asks her sister, Nina, to come home, away from the new Malaysia that has absorbed Singapore in exchange for land as the island nation submerges. Sarawak is willing to accept West Malaysian spouses and children of native Sarawakians, but West Malaysians are reluctant to move as they are fearful of never being trusted and of being thought of as spies. Then in Malaysia, Nina’s 15-year-old daughter receives an official letter from the Ministry of Defence to report for National Service.